Global Diversification Dynamics Since the Jurassic: Low Dispersal and Habitat-Dependent Evolution Explain Hotspots of Diversity and Shell Disparity in River Snails (Viviparidae). (15th February 2020) - Stelbrink, Björn; Richter, Romy; Köhler, Frank; Riedel, Frank; Strong, Ellen E; Van Bocxlaer, Bert; Albrecht, Christian; Hauffe, Torsten; Page, Timothy J; Aldridge, David C; Bogan, Arthur E; Du, Li-Na; et al.
Abstract: The Viviparidae, commonly known as River Snails, is a dominant group of freshwater snails with a nearly worldwide distribution that reaches its highest taxonomic and morphological diversity in Southeast Asia. The rich fossil record is indicative of a probable Middle Jurassic origin on the Laurasian supercontinent where the group started to diversify during the Cretaceous. However, it remains uncertain when and how the biodiversity hotspot in Southeast Asia was formed. Here, we used a comprehensive genetic data set containing both mitochondrial and nuclear markers and comprising species representing 24 out of 28 genera from throughout the range of the family. To reconstruct the spatiotemporal evolution of viviparids on a global scale, we reconstructed a fossil-calibrated phylogeny. We further assessed the roles of cladogenetic and anagenetic events in range evolution. Finally, we reconstructed the evolution of shell features by estimating ancestral character states to assess whether the appearance of sculptured shell morphologies was driven by major habitat shifts. The molecular phylogeny supports the monophyly of the three subfamilies, the Bellamyinae, Lioplacinae, and Viviparinae, but challenges the currently accepted genus-level classification in several cases. The almost global distribution of River Snails has been influenced both by comparatively ancient vicariance and more recent founder events. In Southeast Asia, Miocene dispersal was a main factor in shaping the modern species distributions. A recurrent theme across different viviparid taxa is that many species living in lentic waters exhibit sculptured shells, whereas only one strongly sculptured species is known from lotic environments. We show that such shell sculpture is habitat-dependent and indeed evolved several times independently in lentic River Snails. Considerably high transition rates between shell types in lentic habitats probably caused the co-occurrence of morphologically distinct shell types in several lakes. In contrast, directional evolution toward smooth shells in lotic habitats, as identified in the present analyses, explains why sculptured shells are rarely found in these habitats. However, the specific factors that promoted changes in shell morphology require further work. [b iogeographical analyses; fossil-calibrated phylogeny; fossil-constrained analyses; Southeast Asia; stochastic character mapping.]